Kentin Eşiklerinde Beliren Bir İmkan Olarak Karşılaşma Mekanı - Dündar, Zeynep (Fen Bilimleri Enstitüsü, 2015)
Gündelik hayat farklı aralıklarla meydana gelen karşılaşmalardan oluşur. Gündelik hayatın içine karışan herkes de bu karşılaşmaların -farkında olarak ya da olmayarak- birçok kez parçası olur. Özellikle de kent yaşamı içerisindeki birey, kentlerin çoklu ve karmaşık karakteri nedeniyle devamlı olarak karşılaşmaları deneyimlemektedir. Buradaki problematik nokta bireylerin yaşadıkları karşılaşmaların farkında olmaması nedeniyle karşılaşmanın tarifleyeceği mekanların açığa çıkamayıp saklı kalmasıdır. Günümüzde bireyin serbest zamanları ve çalışma saatleri katı bir sınırla ayrılmayıp birbirinin içine geçmiş bir haldedir. Bunu bir potansiyel olarak görüp bireyin yaşama ve çalışma aralıklarında yeni bir oluşum arayışına gitmek gerekmektedir. Böylece gündelik hayatın monoton yapısını kırmak mümkün olacaktır. Zaten gündelik hayatın akışına kapılmış olan bireyler de bu yapıyı kıracak birtakım arayışların peşindedir. Karşılaşma, mekan üretiminde bir tetikleyici midir? Karşılaşmaya müdahale edilebilirse ondan doğan mekana da müdahale edilebilir mi? Karşılaşma gerçekleşmek için bir mekana ihtiyaç duyar mı yoksa o mekanı hep kendisinde mi taşıyarak gerektiğinde mekanını oluşturur mu? Yoksa var olan bir mekana mı yerleşir? Tez bu sorulara cevap bulmak arayışıyla karşılaşma kavramını bir düşünce aracı olarak ele alarak farklı mekan potansiyellerinin peşine düşmektedir. Bu amaçla tez boyunca tıpkı bir süzgeçten geçirir gibi karşılaşma kavramının açılımından başlayarak teker teker süzülen bilgilerle birlikte karşılaşma mekanı tarifine ulaşacak olan yolun kurulması hedeflenmektedir. Birinci bölümde, tezin problematiği ve yöntemi karşılaşmaların önemini daha güçlü vurgulayabilmek amacıyla karşılaşma kelimesinin kavramsal açılımları ve karşılaşma(ma) durumu üzerinden tariflenmektedir. İkinci bölümde, bir karşılaşmanın gerçekleşebilmesi için gerekli olan hallere bakılmaktadır. Bunun için olmazsa olmaz şart ne ile karşılaşma sorusunun cevabı olan karşılaşmanın katılımcılarıdır. Karşılaşma sadece insanlar arasında yaşanmaz. Karşılaşılan kitap, sanat eseri, manzara ya da bina gibi birçok örnekle de çoğaltılabilecek nesne ya da olgular olarak düşünülmelidir. Ardından nasıl karşılaşıyoruz sorusuna yanıt aranırken bir karşılaşmanın gerçekleşmesi için gerekli olan haller açığa çıkarılacaktır. Haller üzerinden tariflenen karşılaşmanın tetikleyicileri üç ana başlık ve onların alt açılımları şeklinde gruplanmıştır. Bunlar karşılaşma halleri, karşılıklı olma halleri ve eylemlilik halleridir. Karşılaşma halleri tutku, ön-kavrayış ve tesadüf kavramları ile, karşılıklı olma halleri çatışma, uzlaşma, yok sayma ve ağırlama kavramları ile, eylemlilik halleri ise hareket/yürüme, görme/bakma, konuşma/dinleme kavramları ile ilişkilenmektedir. Bu üç hal, hepsinin bir arada olduğu durumlarda bir karşılaşmanın gerçekleşmesine ortam sunmaktadır. Üçüncü bölümde, karşılaşmayı tetikleyen hallerin nerede ve ne şekilde bir mekan oluşumuna yol açtıklarını keşfetmek amacıyla mekansallık ve liminallik kavramları ile birlikte bir okuma gerçekleştirilmektedir. Bu okuma esnasında karşılaşmanın kendisinin bir liminallik ve mekansallık olduğu ortaya çıkmaktadır. Karşılaşmanın bir mekan üretme potansiyeline sahip olup olmadığını anlayabilmek amacıyla karşılaşma ve liminallik durumları ile kurulan mekansallıklar olarak boş vakit mekanı ve üçüncü mekan bir keşif aracı olarak tartışılmaktadır. Böylece karşılaşma mekanının kurulumuna dair ilişkiler vurgulanmaktadır. Dördüncü bölümde, ilk üç bölümden süzülerek gelen tüm bilgiler ile karşılaşmanın mekanının kurulumuna ve tanımlanmasına dair bir söz üretimi üzerine gidilmektedir. Tez kapsamında karşılaşmanın mekanını kent ölçeğinde gerçekleşen karşılaşmaların kurduğu mekansallıklar üzerinden tartışmak tercih edilmiştir. Bunun nedeni kentin aslında karşılaşmalar kurulan ve bu karşılaşmaların tetiklediği etkileşim ve ilişkilerle örülen bir yapıya sahip olmasıdır. Bu amaçla bu bölümde dört örnek üzerinden bir tartışma gerçekleştirilmiştir. Bu örneklerden biri olan New York Halk Kütüphanesi merdivenleri kentteki mevcut karşılaşma mekanlarının analizini yaparken bir diğeri olan Amsterdam‟da bank projesi ise kente müdahalede bulunarak karşılaşmaları tasarlamayı amaçlayan bir örnektir, üçüncü örnek bir sanat enstalasyonu ile gerçekleştirilen deneysel bir çalışma aracılığıyla kamusal alanların nasıl karşılaşmalara açılabileceğini sorgularken, dördüncü örnek ise pop-up olarak adlandırılan ve kentte aniden ve ihtiyaca göre ortaya çıkan, ihtiyaç ortadan kalktıktan sonra iz bırakmadan yok olan mekanları karşılaşma kavramı bağlamında incelemektedir. Son bölümde ise tezin başından itibaren karşılaşma kavramının açılımları ile ortaya çıkan karşılaşma mekanın kurucuları vurgulanmakta ve tezin başında sorulan soruların cevapları tartışılmaktadır. Çıkan sonuçlar tasarımcıya karşılaşma mekanının nasıl tasarlanabileceğine dair bir veriler de sunar. Tez genişlemeye açık bir örüntü olarak değerlendirilmedir. Bu tez kapsamında sadece kensel karşılaşmalara ve ürettikleri mekanlara odaklanılmıştır. Fakat tezin başından itibaren karşılaşma kavramının açılımları ile ortaya çıkan veriler üzerinden yapılacak tartışmalarla yapı ölçeğindeki karşılaşmalara ve onlardan üretilecek olan mekanlara bakmak da mümkündür.

Everday life consists of the encounters happen at different times. People who experience the everyday life -consciously or unconsciously- become the part of these encounters. Especially people that live in the cities experience encounters frequently according to the complex and diverse characteristics of the cities. The problematic point is this: space that defined by encounter cannot be appeared because individuals are unaware of encounters they experienced in their daily life. Nowadays free times and and working hours of individual are not restricted on the contrary they have been merged. This should be seen as a potential to seek for a new space which occurs in the liminality of free time and working hours of individuals. By the way it is possible to break the monotonous structure of everyday life. Already indivuals who are the part of the everyday life seek for some solutions to break this rigid structure. Does the encounter trigger the production of space? Is it possible to intervene the space that occurs from an encounter if the encounter is intervened? Does the encounter need a space to occur or does it carry the space with itself ? Or does it settle into an existing space? In this thesis, encounter concept is approached as a tool to find answers to these questions and to discuss different potentials of space production. Therefore beginning with the conceptual expansions of encounter all the informations will be filtered to reach definition of the space of encounter. In the first section, the problematic of thesis and the methods of it is defined. Thesis is discussed with the conceptual expansions of encounter and the aspect of not to encounter. The second section examines the states which form an encounter. For this reason participants of an encounter which is the answer of what we encounter is a must. An encounter does not only occur between people. The thing that is encountered can be varied as a book, a painting, a scenery or a building etc. When looking for an answer how we encounter the states which ara necessary for an encounter‟s appearing are discussed. The triggers of an encounter are groupped under three main topic and their lower expansions. The main topics are the states of encounter, the states of being to be encountered and the states of action. The states of encounter are related with the concepts of desire, self-perception and coincidence, the states of being to be encountered are related with the concepts of conflict, negotiation, ignorance and entertainment, the states of action are related with the concepts of movement/walking, looking/seeing and listening/talking. If only these three states come together an encounter occurs. In third section, to discover where and how the states that trigger an encounter found a space, a reading is done with the concepts of liminality and spatial. While this reading, encounter is defined as a liminal and spatial state. To understand the potential of encounter for production a space, the space of leisure and the third space which are found with the concepts of liminality an spatial are discussed as an exploration tool. Thus the relations for the founding of a space are emphasised. In fourth section, with all the arguments coming from the first three section it is aimed to discuss the production and meaning of encounter space. Scope of thesis, it is preffered to argue the space of encounter through the encounters that happens in the city scale. The reason is that the city has a structure that is produced by encounters. Encounters trigger the relations and interactions in the city life. In the second part of the fourth section, a discussion is made over the four different examples. One of these is the front steps of New York Public Library. Library is located at the intersection of the 40th ve 42nd streets in Manhattan. According to the study made by Rivlin and her team in 1984, the usage of front steps of the library is examined with the tecniques like observation, survey and interview. The result of the study shows that the steps are used by so many different people all day. Some people who work around the library come to eat their lunch in the afternoon, some people who walk across the library stop and sit for a while, some people come from far places for only spend time at this place. The activities on the steps range such as eating, reading, sunbathing, listening to music, talking with friends, taking a breath, sleeping, watching the scene of the street or performances, shopping from the stands. Encounter uses the urban pattern as a floor with all the urban components such as steps, columns, sculptures, fence, banks to produce its spatiality. Although the steps did not designed for this active use, it became one of the most popular urban space in Manhattan with the spatialiy of encounters. Second example is the bank project in Amsterdam. It is an organizational project hold by BankjesCollectief on first Sunday of the every month. Participants of the organization hire banks or use their own furnitures and set them in front of their houses or shops. The service of the banks range such as selling food or drink, knitting, playing with children, taking dance lessons, gossip. The place and the service of the banks can be learned from the web site of the organization. The encounters and the spaces occur from the encounter spreads over the city by this organization. This project shows the city-dwellers that the urban space is produced, used and shared by themselves. Thus example let us discuss the production of urban space and the alternative use of them according to the space of encounter. Bank project produce its encounter spaces by using the areas between the buildings, the facade of the buildings, pavements, steps and parking areas temporarily. City-dwellers changes the pavements that belong to the city into the extension of their houses or shops. By this way they can produce their spatiality by encountering the city and people. The third example is an installation named “Chance Encounters on the Tiber” which was produced by composer Lisa Bielawa and artist Robert Hammond in 2010. This example is chosen to understand the role of art works for producing the encounter spaces. This works questions how the urban spaces can be open to the encounters. Tiber River is an urban place that is not preffered to spend time by the people in Rome. Hammond decided to put 100 red coloured chairs along the river. The result of the placing chairs shows that the place still do not attract people. A few people came and sat on the chairs because the river is located at lower stage. At the end of the one month, on the last day of the installation, Bielawa‟s musical composition was played by the musicians. The music attracted people walking on the upper level. People came to the river side and sat on the red chairs while listening to music. The installation shows that placing chair is not enough for the encounters until the music is played. At the second part of the installation, they decided to use the area in front of the MAXXI Museum in Rome designed by Zaha Hadid. It was the opening day of the museum. This area has similarities with the Tiber River. They both differs from the Rome‟s classical urban pattern. After the installation, it can be said that this area attracted more people than the Tiber River because it is located on the intersection of the main roads. People carried the chair wherever they wanted to sit. City-dwellers made picnic, talked to each other, had sunbathe, read books on the chairs all the day while listening to music. The other day when the installation left the area, people used the area only for the backstage of their photographs. When the structures that organise the encounters leave, the space of encounter gets lost. The fourth example is pop-up spaces. Pop-up spaces suddenly occur in the city according to an answer for a need in the city life. After the need is lost, the pop-up space leaves there and do not leave traces. This type of spaces can be evaluated as encounter spaces in general terms. All the examples studied in the thesis are pop-up spaces. In last section, all the questions that are asked in the introduction of the thesis are discussed according to the evolutions of the encounter which is discussed in all sections by different point of views. The study leads to think about the mean and the way to product urban spaces when discussing the space of encounter. Thesis should be thought as a pattern which is open to develop. In this study urban encounters and the spaces producted by them are focused but with evolutions on encounter, it is possible to analyze the encounters on different scales.
Space Of Encounter As An Appearing Potential İn The Liminality Of The City
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: karşılaşma; mekan üretimi; kentsel yaşam; mekansallık; liminal; encounter; production of space; city life; spatiality; liminality